Environmental turmoil and firms' core structure dynamism: the moderating role of strategic alliances. Issue 7 (17th July 2019) - Xue, Rui; Qian, Gongming; Qian, Zhengming; Li, Lee
Abstract : Purpose: Much of the extant evidence in the marketing literature posits that firms use strategic alliances to share resources, costs and risks as paths to performance improvements. Drawing from the organizational ecology theory, this study aims to propose a different rationale, namely, that strategic alliances protect a firm's core structure – its stated goals, authority structure, core technologies and marketing strategies – by mitigating the need for hazardous changes in hostile environments. Design/methodology/approach: This study collected quantitative data using market survey and analyzed the data with the regression method. Findings: Using Chinese firms in three technology industries as the research setting, this research finds a positive and significant relationship between environmental hostility and core structure dynamism. Although strategic alliances themselves have no direct bearing on core structure dynamism, they are found to moderate this relationship negatively, that is, strategic alliances attenuate the relationship between environmental hostility and structural changes. Research limitations/implications: This paper argues that strategic alliances have significant moderating effects on firm performance, that is, firms use strategic alliances to outsource competence to partners and, thus, avoid internal turmoil. However, the moderating effect alone cannot explain the complexity of strategic alliances. There could exist other effects that remain unknown. In addition, individual-level factors could have significant impacts on strategic alliance management. Future studies should look into these issues to advance the authors' knowledge on strategic alliances. Practical implications: The findings of this study show that managers should outsource competence to partners when they experience turmoil in markets. Adapting to market turmoil internally could lead to market failure. Originality/value: This study provides a new rationale for strategic alliances, that is, firms use strategic alliances to reduce market uncertainty. This rationale has not been reported in the existing literature.